2017
DOI: 10.1371/journal.pone.0179489
|View full text |Cite
|
Sign up to set email alerts
|

When habitat matters: Habitat preferences can modulate co-occurrence patterns of similar sympatric species

Abstract: Disentangling the role of competition in regulating the distribution of sympatric species can be difficult because species can have different habitat preferences or time use that introduce non-random patterns that are not related to interspecific interactions. We adopted a multi-step approach to systematically incorporate habitat preferences while investigating the co-occurrence of two presumed competitors, morphologically similar, and closely related ground-dwelling birds: the brown tinamou (Crypturellus obso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 53 publications
3
41
0
Order By: Relevance
“…), Brown Tinamous ( Crypturellus obsoletus ), and Tataupa Tinamous ( Crypturellus tataupa ; Estevo et al. ), all of which show similar diurnal and crepuscular activity as described for the three tinamous in our study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…), Brown Tinamous ( Crypturellus obsoletus ), and Tataupa Tinamous ( Crypturellus tataupa ; Estevo et al. ), all of which show similar diurnal and crepuscular activity as described for the three tinamous in our study.…”
Section: Discussionsupporting
confidence: 81%
“…, Estevo et al. ) and, among tinamous, daily activity patterns have been described for Little Tinamous (Mosquera‐Muñoz et al. ), Black Tinamous ( Tinamus osgoodi ; Negret et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Largebodied terrestrial birds have been found to associate with either riparian forest systems or terra firme interior forest (Martínez-Morales 1999, Haugaasen andPeres 2008). Elevation can be important for tinamou distributions (Estevo et al 2017) and has been suggested as a driver of cracid populations (Kattan et al 2016). Camera position on or off trail influences detection probability of rainforest vertebrates (Harmsen et al 2010, Kays et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Two hypotheses could explain this pattern of co-occurrence: i) slightly different environmental requirements among species (e.g. Estevo et al 2017), with C. guaporensis having greater ability to cope with longitudinal changes in environmental conditions than C. epakros; or ii) competitive interactions between both Chalceus species, resulting in the observed slight overlap (with uneven abundances) at their limits of distribution (Brown and Wilson 1956;Hutchinson 1959;Davies et al 2007).…”
Section: Discussionmentioning
confidence: 99%